The Routledge handbook of language and digital communication - Georgakopoulou, Alexandra; Spilioti, Tereza (London Routledge, 2016)
"The Routledge handbook of language and digital communication provides a comprehensive, state-of-the-art overview of language-focused research on digital communication, taking stock and registering the latest trends that set the agenda for future developments in this thriving and fast-moving field. The contributors are all leading figures or established authorities in their areas, covering a wide range of topics and concerns in the following seven sections: methods and perspective ; language resources, genres, and discourses ; digital literacies ; digital communication in public, digital selves and online-offline lives ; communities, networks, relationships ; new debates and further directions. This volume showcases critical syntheses of the established literature on key topics and issues and, at the same time, reflects upon and engages with cutting edge research and new directions for study (as emerging within social media). A wide range of languages are represented, from Japanese, Greek, German and Scandinavian languages, to computer-mediated Arabic, Chinese and African languages." -- Provided by publisher
Introduction by Alexandra Georgakopoulou and Tereza Spilioti -- Approaches to language variation Lars Hinrichs -- Network analysis John C. Paolillo -- Digital ethnography Piia Varis -- Multimodal analysis Carey Jewitt -- Digital genres and processes of remediation Theresa Heyd -- Style, creativity and play Yukiko Nishimura -- Multilingual resources and practices in digital communication Carmen Lee -- Digital discourses: a critical perspective Tereza Spilioti -- Digital media and literacy development Michele Knobele and Colin Lankshear -- Vernacular literacy: orthography and literacy practices Josh Iorio -- Texting and language learning Sam Waldron, Nenagh Kemp and Clare Wood -- Digital media in workplace interactions Erika Darics -- Digital advertising Helen Kelly-Holmes -- Corporate blogging and corporate social media Cornelius Puschmann and Rebecca Hagelmoser -- Twitter: design, discourse, and the implications of public text Lauren Squires -- The role of the body and space in digital multimodality Elizabeth Keating -- Second life: language and virtual identity Ashraf R. Abdullah -- Online multiplayer games Lisa Newon -- Relationality, friendship, and identity in digital communication Sage Lambert Graham -- Online communities and communities of practice Jo Angouri -- Facebook and the discursive construction of the social network Caroline Tagg and Philip Seargeant -- Youtube: language and discourse practices in participatory culture Jannis Androutsopoulos and Jana Tereick -- Translocality Samu Kytola -- Social reading in a digital world Naomi S. Baron -- New frontiers in interactive multimodal communication Susan C. Herring -- Moving between the big and the small: identity and interaction in digital contexts Ruth Page -- Surveillance Rodney H. Jones -- Choose now! Media, literacies, identities, politics Charles M. Ess
Includes bibliographical references (pages 415-416) and index.
Keywords: Language and languages -- Computer network resources -- Handbooks, manuals, etc; Digital communications -- Handbooks, manuals, etc